Patient Reports as Stories of Clinical Work: Narrative and Work in Neuroradiology - Rooksby, J.; Kay, S. (Methods of Information in Medicine, 2003)
Objective: This paper describes the connections between the radiology report and clinical work and considers the implications for computerisation.Method: A story representation is described that allows consideration of the radiology report as an active unit of narrative rather than a passive collection of data. This paper draws upon the results of a qualitative study of a neuroradiology department.Results and Conclusion: Radiology reports recount a patient condition but also represent and influence clinical work.
Keywords: Narrative; story; radiology report; clinical work process